Nipple-Sparing Mastectomy in Patients with Previous Breast Surgery: Comparative Analysis of 775 Immediate Breast Reconstructions. Issue 6 (June 2015) - Frederick, Michael J.; Lin, Alex M.; Neuman, Robert; Smith, Barbara L.; Austen, William G.; Colwell, Amy S.
Abstract : Background: An increasing number of women are candidates for nipple preservation with mastectomy. It is unclear how previous breast surgery impacts nipple-sparing mastectomy and immediate breast reconstruction. Methods: A single-institution retrospective review was performed between June of 2007 and June of 2013. Results: Four hundred forty-four patients underwent 775 immediate breast reconstructions after nipple-sparing mastectomy. Of these, 160 patients and 187 reconstructions had previous breast surgery, including 154 lumpectomies, 27 breast augmentations, and six reduction mammaplasties. Two hundred eighty-four patients with 588 reconstructions without previous breast surgery served as the control group. The previous breast surgery patients were older (49.6 years versus 45.8 years; p < 0.001) but otherwise had similar demographics. Previous breast surgery reconstructions were more often unilateral, therapeutic, and associated with preoperative radiotherapy ( p < 0.001 for each). Extension of breast scars was common with previous breast surgery, whereas the inframammary incision was most frequent if no scars were present ( p < 0.001). Multivariate regression analysis showed that previous breast surgery was not a significant risk factor for ischemic complications or nipple loss. Subgroup analysis showed extension of prior irradiated incisions was predictive of skin flap necrosis (OR, 9.518; p = 0.05). A higher number of lumpectomy patients had preoperative radiotherapy (41 versus 11; p < 0.001), and patients with breast augmentation had more single-stage reconstructions (85.2 percent versus 62.9 percent; p = 0.02). Conclusion: Nipple-sparing mastectomy and immediate reconstruction can be performed in patients with prior breast surgery with no significant increase in nipple loss or ischemic complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Coding Perspective for this article is on page 961e.